STUDI PATOGENESIS PENYAKIT JEMBRANA SAPI BALI BERDASARKAN KARAKTERISTIK SELTERINFEKSI PADA JARINGAN LIMFOID DAN DARAH TEPI - Berata, I Ketut (Buletin Veteriner Udayana, 2012)
The aim the research is to studi pathogenesis of Jembrana disease on Bali cattlebased on the characteristic of infected cells in lymphoid tissues and peripheral bloodmononuclear cells. The healthy Bali cattle was inoculated with Jembrana disease virus(JDV) (BBVet collection). After the second day of fever, the peripheral blood of experimental cattle was took jugularis vein. Lymphocyte cells from the peripheral bloodwas isolated by picoll-paque gradient method. Then the experimental cattle was necropsied.The spleen, praescapularis lymphnode and praefemoralis lymphnode were took byaseptically, thenits were processed for to histopathological preparation. For to examine thepercentage of the infected cells in lymphoid organs, the part of each lymphoid tissues weremade suspension in phosphat buffer saline, then it was made smear preparation on theobject glass. Those peripheral lymphocyte cells, lymphocyte smears and histopathologicalpreparation were stained by indirect immunoperoxidase technique. The JDV infected cellswas appeared brown color. The intensity of brown color was examined for to determinedegree of the infection.The result showed that percentage of JDV infected cells in bothspleen andlymphnodes are similarly i.e. average 9,5%. Percentage of the JDV infected cellson peripherallymphocyte cell was average 7%. Based on the intensity of brown color wasappeared that the JDV infected cells from the lymphnodes were stronger than from spleen.The conclusion is the most of the port d‘entry JDV is through the subcutaneus route.
Keywords: Pathogenesis, Jembrana disease virus, Lymphoid organ